Passivity Versus Unilateral Angular Misfit: Evaluation of Stress Distribution on Implant-Supported Single Crowns: Three-Dimensional Finite Element Analysis - Gomes, Erica Alves [UNESP]; Assunção, Wirley Goncalves [UNESP]; Ricardo Barao, Valentim Adelino [UNESP]; Delben, Juliana Aparecida [UNESP]; Rocha, Eduardo Passos [UNESP]; Sousa, Edson Antonio Capello [UNESP] (Lippincott Williams & Wilkins, 2010)
The aim of this study was to evaluate the effect of unilateral angular misfit of 100 Km on stress distribution of implant-supported single crowns with ceramic veneering and gold framework by three-dimensional finite element analysis. Two three-dimensional models representing a maxillary section of premolar region were constructed: group 1 (control)-crown completely adapted to the implant and group 2-crown with unilateral angular misfit of 100 Km. A vertical force of 100 N was applied on 2 centric points of the crown. The von Mises stress was used as an analysis criterion. The stress values and distribution in the main maps (204.4 MPa for group 1 and 205.0 MPa for group 2) and in the other structures (aesthetic veneering, framework, retention screw, implant, and bone tissue) were similar for both groups. The highest stress values were observed between the first and second threads of the retention screw. Considering the bone tissue, the highest stress values were exhibited in the peri-implant cortical bone. The unilateral angular misfit of 100 Km did not influence the stress distribution on the implant-supported prosthesis under static loading.
Keywords: Prosthesis; dental implants; misfit; superstructure materials; finite element analysis